2010
DOI: 10.1007/s10584-010-9799-4
|View full text |Cite
|
Sign up to set email alerts
|

Can ocean iron fertilization mitigate ocean acidification?

Abstract: Ocean iron fertilization has been proposed as a method to mitigate anthropogenic climate change, and there is continued commercial interest in using iron fertilization to generate carbon credits. It has been further speculated that ocean iron fertilization could help mitigate ocean acidification. Here, using a global ocean carbon cycle model, we performed idealized ocean iron fertilization simulations to place an upper bound on the effect of iron fertilization on atmospheric CO 2 and ocean acidification. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 10 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…2008; Matear & Elliott, 2004) and ocean acidity (Cao & Caldeira, 2010). Impacts on the food web are hard to predict (Strong et al, 2009) and in case of overfertilization, excessive blooms could cause patches of oxygen depletion (anoxia) (Russell et al, 2012) or toxicity (Denman, 2008).…”
mentioning
confidence: 99%
“…2008; Matear & Elliott, 2004) and ocean acidity (Cao & Caldeira, 2010). Impacts on the food web are hard to predict (Strong et al, 2009) and in case of overfertilization, excessive blooms could cause patches of oxygen depletion (anoxia) (Russell et al, 2012) or toxicity (Denman, 2008).…”
mentioning
confidence: 99%
“…Such unpredictability also connects to ambiguity in that there will be different determinations of appropriate interventions where some question how much to "meddle" in the environment for the sake of human needs or otherwise. The case of proposed iron fertilization to combat ocean acidification elucidates the challenges that arise when moving from theoretical models [99] to (unauthorized) experimentation-and resultant controversy-at sea (see [100] for summary).…”
Section: Building With Nature (High Intervention Anthropocentric)mentioning
confidence: 99%
“…Earlier studies, which used biogeochemical cycle models without the explicit iron cycle, implicitly modeled the effect of iron fertilization, e.g., by depleting near-surface phosphate (Sarmiento and Orr 1991). These studies tended to report optimistic potentials for atmospheric CO 2 drawdown, and some reported approximately 100 ppm of CO 2 drawdown (Joos et al 1991;Cao and Caldeira 2010b). As the models improved, however, estimates of the potential were revised downward in most studies.…”
Section: Modeling Of Cdrmentioning
confidence: 99%